2017
DOI: 10.1111/ijag.12319
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion coefficient controlling crystal growth in a silicate glass‐former

Abstract: One of the most relevant open issues in glass science refers to our ignorance concerning the nature of the diffusing entities that control crystal nucleation and growth in non‐crystalline materials. This information is very relevant because all the existing nucleation and growth equations account for the diffusion coefficient (DU) of these unknown entities. In this article, we measured the shear viscosity (η) and the crystal growth rates of a supercooled diopside liquid (CaMgSi2O6) in a wide temperature range.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…We are not aware of any other direct experimental study of diffusion in silicate supercooled liquids mentioning the breakdown of the Eyring relation. Several studies (Reinsch et al, 2008;Nascimento et al, 2011;Schmelzer et al, 2015) have shown that the energetics of crystal growth do not follow Eyring relation close to the glass transition, but the interpretation of the diffusivity coefficient in the law of crystal growth is still subject to debate (Cassar et al, 2018). NMR 2D MAS measures of the Q 3 − Q 4 exchange rates showed that the Eyring relation was verified up to 55 • C above the glass transition in K 2 Si 4 O 9 liquids.…”
Section: Arrhenian Behavior Of Eigenvaluesmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any other direct experimental study of diffusion in silicate supercooled liquids mentioning the breakdown of the Eyring relation. Several studies (Reinsch et al, 2008;Nascimento et al, 2011;Schmelzer et al, 2015) have shown that the energetics of crystal growth do not follow Eyring relation close to the glass transition, but the interpretation of the diffusivity coefficient in the law of crystal growth is still subject to debate (Cassar et al, 2018). NMR 2D MAS measures of the Q 3 − Q 4 exchange rates showed that the Eyring relation was verified up to 55 • C above the glass transition in K 2 Si 4 O 9 liquids.…”
Section: Arrhenian Behavior Of Eigenvaluesmentioning
confidence: 99%
“…Email address: emmanuelle.gouillart@saint-gobain.com (Emmanuelle Gouillart) glasses (Zhang et al, 2010). In the glass industry 4 as well as in magmatic processes, chemical diffusion at high temperature plays an important role for crystal nucleation and growth (Roskosz et al, 2005(Roskosz et al, , 2006Nascimento et al, 2004;Reinsch et al, 2008;Nascimento et al, 2011;Cassar et al, 2018), for mineral dissolution (Edwards and Russell, 1996;Liang, 1999;Acosta-Vigil et al, 2002Chen and Zhang, Preprint 2008) and for phase separation (Mazurin and Streltsina, 12 1972;Bouttes et al, 2015). Closer to the glass tran-13 sition, diffusion controls ionic exchanges for strengthened glasses (Smedskjaer et al, 2011;Vargheese et al, 2014), and exchanges between glass substrates and thin films (Fonné et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka demonstrated that T LML only exists because a breakdown of the Stokes-Einstein (SE) relation takes place above the T g . This breakdown is a decoupling of the diffusion coefficients controlling crystal growth and viscous flow, often reported to occur at a temperature T d somewhat above T g , [20][21][22][23][24] Tanaka stressed that his explanation differs from the "crystallization" resolution proposal of Kauzmann because the physics behind them is different: the decoupling at T d , which was not known at the time of Kauzmann, was the key to deriving his conclusion. He suggested that this decoupling is caused by dynamic heterogeneities 25,26 that accelerate and destabilize an equilibrium supercooled liquid state against crystallization at low temperatures.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Several works 44,48 successfully connected D U with the shear viscosity of the supercooled liquid using the Stokes-Einstein-Eyring equation, 49 but this connection breaks down for temperatures below 1.1-1.2T g . 44,[50][51][52] Fortunately, however, this break is not relevant for this particular work because we will be dealing with crystallization at much higher temperatures, near to the nose of the TTT curves, which are close to T L . Equation 2 shows that on a TTT curve, the time needed to reach a certain surface crystallized fraction at each temperature is given by…”
Section: Classical Crystal Growth Models For Inorganic Glassesmentioning
confidence: 99%